(untitled) (Revista de Ciências Agroveterinárias, 2017)
Plant cutting is a widely used propagation method for olive trees. Its viability depends on the capacity for the adventitious root formation of each species. Nevertheless, it is necessary to study the different characteristics of this process. The purpose of this study was to evaluate the influence of substrates on the rooting of semi hardwood stem cuttings of ten olive tree cultivars. Middle sized branches were collected from mother plants located in the Germplasm Bank of EPAMIG in Maria da Fé, MG, Brazil, and cuttings were prepared of approximately 12 cm in length, with 4-6 internodes, maintaining four leaves in the apical region. A completely randomized experimental design was used, with tree replications and 20 cuttings per plot. The experiment was conducted in greenhouses, in rooting plant beds containing a perlite and sand substrate with controlled intermittent water mist. After installation of the experiment, treatment was carried out with copper oxychloride solution at 3% to prevent possible fungus attacks. Evaluations were performed 70 days after cutting of the varieties. There was variation in rooting of olive tree cultivar cuttings. Better performance of sand was observed in the production of cuttings of olive tree cultivars Alto D’Ouro, JB1 and Galega which were also the cultivars that stood out among the genotypes studied.